Sistem Pendeteksi Pencemaran Udara Ambien Di Kawasan Lumpur Lapindo Dengan Menggunakan Logika Fuzzy - Reza Hastuti; Edita Rosana Widasari; Barlian Henryranu Prasetio (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Lapindo hot mud in disaster area affected the quality of ambient air. Monitoring ambient air pollution in affected area of Lapindo hot mud performed by classifying the level of ambient air pollution. The classification also describes the impact that can occur from each category based on the level of ambient air pollution. Based on the result of testing system with samples from three affected areas of Lapindo hot mud, fuzzy output has the accuracy 84% in Siring Barat village, 93% in Mindi Village, and 95% in Jatirejo village by using methane gas, dust particle (PM10), and CO gas as parameters. Furthermore, Jatirejo village has an average index value of air quality is about 54.43 with an average methane concentration is about 4.60 ppm. Therefore, Mindi village has an average index of air quality is about 41.95 with an average methane concentration is about 2.40 ppm and Siring Barat village has an average index of air quality is about 37.00 with an average methane concentration is about 15.18 ppm. The analysis result shows the concentration of methane exceeds the threshold level even the air quality index in a safe range, It shows that the level of ambient air pollution in those three affected areas of Lapindo hot mud is in Hazardous level.